PEMELIHARAAN HUBUNGAN PASANGAN SUAMI ISTRI TULI-DENGAR DALAM COMMITTED ROMANTIC RELATIONSHIP - Martina Aurelia Carissa; Turnomo Rahardjo; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Differences in hearing conditions and ways of communication in the committed romantic relationship of Deaf-hearing couples encourage individuals to conduct adjustments and apply relationship maintenance behaviors to achieve the desired ideal point of the relationship. On the other hand, these differences have the potential to cause miscommunication and conflict in Deaf-hearing couples. This study aims to understand the maintenance in committed romantic relationships of Deaf-hearing couples and to describe the conflicts, dialectics, and the conflict resolution in committed romantic relationships. The theories that are used in this research are Relational Dialectics Theory and Equity Theory. This study uses the interpretive paradigm with a phenomenological approach and data collection method of in-depth interviews conducted with six individuals from three Deaf-hearing couples. The result of this study reveals that the communication adjustments made by Deaf and hearing individuals in their relationships take place from the development until maintenance stage of the relationships. Each individual accomodates their partner’s way of communication by using verbal communication and sign language in daily communication context. Each Deaf-hearing couple apply relationship maintenance to achieve the desired ideal relationship, prevent conflicts, and maintain commitment in their marriages. Other than that, the difference in hearing conditions is not the main conflict object but is a cause of miscommunication and small conflicts in Deaf-hearing couples. Conflict resolution in Deaf-hearing couples is conducted through several strategies such as withdrawal, turn-taking, and the involvement of a mediator. Based on the results above, recommendations for future research is to examine how miscommunication arises when hearing partners act as sign language translators, how Deaf individuals sacrifice by prioritizing the use of verbal communication, and to apply mixed methods to study Deaf-hearing committed romantic relationship.